The Shangai Global Ranking of Academic Subject: Room for improvement - Krauskopf Poblete, Erwin Humberto. (El Profesional de la Información, 2021)
Global university rankings have achieved public popularity as they are portrayed as an objective measure of the quality of higher education institutions. One of the latest rankings is the Shanghai Global Ranking of Academic Subjects, which classifies institutions according to five fields –Engineering, Life Sciences, Medical Sciences, Natural Sciences and Social Sciences– which are divided into 54 subjects. Despite being introduced in 2017, no study has analyzed the methodology applied by this ranking. The results of our analysis show that the methodology currently used by the Shanghai Global Ranking of Academic Subjects presents several issues, which negatively affect a large proportion of universities around the world. Needless to say, if the Shanghai Global Ranking of Academic Subjects is meant to be global, it needs to expand its surveys to countries located in the Global South.
Keywords: ARWU; Shanghai ranking; Academic subjects; WoS; JCR; Topics; Issues; Disciplines; Rankings; Classifications; Universities; Higher education; Institutions; Bibliometrics; Research performance; Research evaluation; Critical perspective; Flaws; Indicators; Global south; Categories